2022
DOI: 10.1155/2022/2262983
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Flipping an English Reading Course: Focus on Reading Gains and Anxiety

Abstract: The aim of this research was to explore the effect of flipped classroom on English as a Foreign Language (EFL) learners’ reading skill and reading anxiety. For this purpose, a sample of 44 Iranian EFL learners was recruited and randomly assigned to a flipped group (N =23) and a non-flipped group (N =21). Using a quasi-experimental design, the researchers employed an experimental group that received flipped instruction and a control group that were instructed based on the regular method for a period of four mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Then, the Servlet will fill the processed response results into the relevant attributes of the corresponding object Servlet response. The return process is in the charge of the container where it is located, and the content that the user can understand will be parsed by the browser and displayed in a corresponding way [12], as shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the Servlet will fill the processed response results into the relevant attributes of the corresponding object Servlet response. The return process is in the charge of the container where it is located, and the content that the user can understand will be parsed by the browser and displayed in a corresponding way [12], as shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous investigations have explored the influence of flipped classroom methodologies on the reading proficiencies of EFL students and associated variables. In their study, Mohammaddokht and Fathi (2022) noted that flipped instruction produced substantial enhancements in EFL reading capabilities while concurrently alleviating reading-related apprehension. These findings imply the potential utility of flipped instruction in the context of EFL reading courses.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Prior to, during, or after reading a text, learners can leverage various techniques to enhance their language proficiency ( Jiang et al, 2022 ). These include consulting dictionaries to clarify unfamiliar words, utilizing contextual clues to predict and deduce meanings, engaging in discussions with peers to elicit insights, and employing effective organizational strategies such as rehearsal, rereading, and summarization ( Mohammaddokht and Fathi, 2022 ). By employing a range of cognitive and metacognitive strategies, learners optimize their reading experience and foster a deeper understanding of the text ( Kintsch, 2012 ; Fischer and Yang, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…al (2022) suggested that flipped teaching raised students' awareness related to reading strategies. Flipping the reading skills class also helps learners to lower their reading anxiety and perform better regarding EFL reading (Mohammaddokht & Fathi, 2022). Sun (2017) discovered that flipped classroom approach helped learners to use varied learning strategies.…”
Section: The Flipped Classroom For Language Learningmentioning
confidence: 99%